The MDM2 ligand Nutlin-3 differentially alters expression of the immune blockade receptors PD-L1 and CD276 - Ruidong Li (Cellular & Molecular Biology Letters, 2020)
Abstract Background The links between the p53/MDM2 pathway and the expression of pro-oncogenic immune inhibitory receptors in tumor cells are undefined. In this report, we evaluate whether there is p53 and/or MDM2 dependence in the expression of two key immune receptors, CD276 and PD-L1. Methods Proximity ligation assays were used to quantify protein-protein interactions in situ in response to Nutlin-3. A panel of p53-null melanoma cells was created using CRISPR-Cas9 guide RNA mediated genetic ablation. Flow cytometric analyses were used to assess the impact of TP53 or ATG5 gene ablation, as well as the effects of Nutlin-3 and an ATM inhibitor on cell surface PD-L1 and CD276. Targeted siRNA was used to deplete CD276 to assess changes in cell cycle parameters by flow cytometry. A T-cell proliferation assay was used to assess activity of CD4+ T-cells as a function of ATG5 genotype. Results CD276 forms protein-protein interactions with MDM2 in response to Nutlin-3, similar to the known MDM2 interactors p53 and HSP70. Isogenic HCT116 p53-wt/null cancer cells demonstrated that CD276 is induced on the cell surface by Nutlin-3 in a p53-dependent manner. PD-L1 was also unexpectedly induced by Nutlin-3, but PD-L1 does not bind MDM2. The ATM inhibitor KU55993 reduced the levels of PD-L1 under conditions where Nutlin-3 induces PD-L1, indicating that MDM2 and ATM have opposing effects on PD-L1 steady-state levels. PD-L1 is also up-regulated in response to genetic ablation of TP53 in A375 melanoma cell clones under conditions in which CD276 remains unaffected. A549 cells with a deletion in the ATG5 gene up-regulated only PD-L1, further indicating that PD-L1 and CD276 are under distinct genetic control. Conclusion Genetic inactivation of TP53, or the use of the MDM2 ligand Nutlin-3, alters the expression of the immune blockade receptors PD-L1 and CD276. The biological function of elevated CD276 is to promote altered cell cycle progression in response to Nutlin-3, whilst the major effect of elevated PD-L1 is T-cell suppression. These data indicate that TP53 gene status, ATM and MDM2 influence PD-L1 and CD276 paralogs on the cell surface. These data have implications for the use of drugs that target the p53 pathway as modifiers of immune checkpoint receptor expression.